Exploring the Impact of Pricing Strategies and Retail Environments on Halal Food Product Sales in the Indonesia Marketplace - Rizki Adi Puspita Sari; Fildzah Yumni Shabrina; Siti Rochaeni (Cita konsultindo, 2024)
The shift in shopping culture in the digital era has revolutionized the way transactions are conducted, particularly in the realm of shopping known as e-commerce. Indonesia, being one of the countries with the world's largest Muslim population, has become a substantial consumer market. The halal certification of a product has become an essential requirement, especially for food products. One e- commerce platform that facilitates the public in finding fully certified halal products is Tokopedia. Indicators that influence sales include price, promotion, quality, product, and distribution channels. However, there is a phenomenon on the Tokopedia platform that contradicts this theory, where, for products with the same specifications, the price might not significantly impact the sales level, even with varying types of stores. This research employs a quantitative descriptive method. Secondary data sources are gathered from the official Tokopedia website and literature. Data collection is carried out in a 32-day time frame. The analysis method used is panel data regression analysis, facilitated by e-views 12 as the data processing tool. The research findings reveal that Price and Store Type jointly affect the sales of halal food products on Tokopedia, with a probability value of F-statistic (0.042) < 0.05. From the outcome of the Random Effect Model regression, the coefficient of determination stands at 23.6%. Partially, the price variable does not have a significant impact on the sales of halal food products on Tokopedia, with a probability value of t-statistic for price: 0.54 > 0.05. On the other hand, the store type variable has a significant impact on the sales of halal food products on Tokopedia, with a probability value of t- statistic: 0.02 < 0.05.